MODERN METHODS FOR EXAMINATION AND TREATMENT OF CHRONIC PERIODONTITIS (KIUT Publication, 2025)
Oral health plays an important role in a person’s overall well-being. The health of the teeth and surrounding gum tissues is not only essential for proper chewing function but is also directly linked to the functioning of the cardiovascular, endocrine, and immune systems. Periodontitis is a chronic inflammatory disease of the gums and supporting tissues, leading to the gradual destruction of the structures that hold the teeth in place.